Analisis Faktor-Faktor yang Mempengaruhi Calon Konsumen dalam Memilih Jasa Makeup Artist (MUA) di Surabaya - Shalsyabilla Marsya Addilia; Nia Kusstianti; Octaverina Kecvara Pritasari; Sri Dwiyanti (Jurnal Tata Rias, 2025)
Abstract of Makeup Artist (MUA) services in Indonesia, especially in large cities like Surabaya, has seen remarkable growth in recent years. This study aims to identify which factors are most influential in the decision-making process of potential consumers. The chosen research method is descriptive survey with correlation analysis, and data collection techniques are performed through questionnaires. This research was conducted in Surabaya by distributing questionnaires using a non-probability sampling method with purposive sampling, which refers to samples based on research needs with 50 respondents. The research findings include (1) an overview of the research location, (2) an overview of the respondents that includes age, gender, place of residence, and profession, as well as (3) data regarding factors influencing potential consumers obtained through validity tests and reliability tests that show all variables are reliable and the results of descriptive analysis. The results of this study indicate that there are seven elements influencing potential consumers' decisions in choosing Makeup Artist (MUA) services in Surabaya, with the dominant factor influencing potential consumers in choosing Makeup Artist (MUA) services being the product and service factors. Through these findings, it is hoped that Makeup Artists (MUA) in Surabaya can continue to maintain and improve the quality of consumer services.